Umpire home bias in Major League Baseball - Hsu, M. (Journal of Sports Economics, 2024)
This paper studies whether Major League Baseball umpires displayed home bias in their pitch calls, using data on pitch call accuracy from the 2010-2019 seasons to isolate evaluator bias from player performances. The main findings are consistent with umpire home bias, as home batters on average received more called balls on actual ball pitches and fewer called strikes on actual strike pitches, which work in their favor. The bias is not entirely explained by umpire, player, or stadium characteristics, nor is it attributable to umpiring inconsistencies.